ANALISIS RISISKO KESEHATAN PAJANAN BENZENA DI INDUSTRI PERCETAKAN X KOTA SEMARANG - Dayu Febriantika; Sulistyani Sulistyani; Budiyono Budiyono (Jurnal Kesehatan Masyarakat (Undip), 2017)
Printing Industry X Semarang is one of the industries that use chemicals containing benzene in the production process. Accumulation of benzene concentration in production room can cause health problem, both carcinogenic or noncarcinogenic. The purpose of this research was to analyze the health risks of exposure to benzene in the Printing Industry X Semarang. The design of this research is observational descriptive with Environmental Health Risk Analysis (EHRA) approach. The population of workers in the printing Industry X was 14, then used as a sample of research. Data analysis using the stages of EHRA including hazard identification, dose-response analysis, exposure assessment, and risk characterization. The result showed the average concentration of benzene that inhaled was 0,422 mg/m3, with an average weight of workers was 64 Kg. Workers exposed to benzene 8 hours per day, in 288 days a year. The average duration of exposure is 7,6 years. The conclusion is benzene concentration at Printing Industry X Semarang can lead noncarcinogenic risk for lifetime exposure. Workers are also at risk of carcinogenic effects, with ECR values already exceed 10-4 to realtime as well as lifetime exposure. Advice to Manager printing industry should provide personal protective equipment such as respirator for workers.